2009
DOI: 10.1111/j.1600-0722.2009.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathectomy suppresses tumor growth and alters gene‐expression profiles in rat tongue cancer

Abstract: Sympathetic nerves are known to affect carcinogenesis. Recently we found that sympathetic denervation decreases the size of rat tongue tumors. To identify genes involved in rat tongue carcinogenesis and to study the effect of sympathetic nerves on these genes, we compared gene-expression profiles in normal rat tongue (control) and in tumor-induced tongues with (SCGx) and without (Sham) bilateral sympathectomy. Significance analysis of microarrays revealed 280 genes (168 up-regulated, 112 down-regulated) that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
0
27
0
2
Order By: Relevance
“…Stimulatory eff ect of the sympathetic nervous system on the tumor growth and development of metastasis has been further supported by experimental and clinical studies, in which sympathetic neurotransmission was attenuated or eliminated (Raju et al 2009;Sloan et al 2010;Barron et al 2011;Lackovicova et al 2011;Magnon et al 2013). Based on these facts, it has been suggested that interventions reducing the eff ect of the sympathetic neurotransmitters may represent a potential adjuvant therapy in oncological patients (Schuller 2010;Powe and Entschladen 2011;Tang et al 2013).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Stimulatory eff ect of the sympathetic nervous system on the tumor growth and development of metastasis has been further supported by experimental and clinical studies, in which sympathetic neurotransmission was attenuated or eliminated (Raju et al 2009;Sloan et al 2010;Barron et al 2011;Lackovicova et al 2011;Magnon et al 2013). Based on these facts, it has been suggested that interventions reducing the eff ect of the sympathetic neurotransmitters may represent a potential adjuvant therapy in oncological patients (Schuller 2010;Powe and Entschladen 2011;Tang et al 2013).…”
mentioning
confidence: 80%
“…For example, chemical sympathectomy performed by 6-OHDA attenuated the incidence of N-methyl-N´-nitro-N-nitrosoquanidine (MNNG) induced gastric cancer in rats (Tatsuta et al 1992), inhibited the growth pattern of LPC-1 plasmacytoma tumors in mice (Grzanna et al 1985), and also decreased the incidence of intra-abdominal fi brosarcoma tumors in rats and prolonged their survival (Lackovicova et al 2011). Similarly, bilateral surgical sympathectomy in rats resulted in the development of significantly smaller and less invasive tongue tumors than in sham-operated animals (Raju et al 2007;Raju et al 2009). Moreover, pre-treatment of tumor-bearing rats with β-blockers signifi cantly reduced the development of tumors in stressed animals as well as development of metastases aft er surgical removal of the tumor mass (Sloan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of reduced sympathetic activity on tumor growth has been widely documented. It was found out that bilaterally sympathectomized rats developed significantly smaller and less invasive tongue tumors than the animals of sham-operated group (Raju et al, 2007(Raju et al, , 2009. Likewise, in a model where mammary tumors were induced subcutaneously in a sympathetically denervated ear, the tumor growth was attenuated approximately by over 50% compared with the contralateral induction in intact ear.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the growth of oral cancers was significantly inhibited by sympathectomy [14]. This impairment of tumor growth induced by denervation was associated with changes in multiple processes, including alteration of the VEGF pathway [15]. Importantly, the sympathetic activity is known to be stimulated by hypoxic conditions [16].…”
Section: Introductionmentioning
confidence: 98%